2019
DOI: 10.29309/tpmj/2019.26.11.3396
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and fetomaternal outcome in pregnancy with thrombocytopenia.

Abstract: Objectives: To find out the risk factors and their effects on mother and fetus in pregnancy with thrombocytopenia. Study Design: Cross sectional study. Setting: Department of Obstetrics and Gynaecology at Liaquat University Hospital Hyderabad. Period: Six months (1st July 2016 to 31st December 2016). Material and Methods: Total 96 patients with gestational age >24 weeks having platelet count below 150X109/L were included in the study. Patients admitted throughout patient clinic department of obstetrics &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…In our study, around 21.33% (n=150) of women had preeclampsia, followed by hypertension and anemia (10.0% each, n=150) which was comparable to the study by Padmawar et al [ 2 ]. This is in contrast to the work of Qureshi et al in which preeclampsia was observed in 14.6% (n=86) cases [ 3 ]. The variation may be due to differences in timing of presentation on which the diagnosis is largely dependent, besides severity of thrombocytopenia and the association with other abnormalities.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, around 21.33% (n=150) of women had preeclampsia, followed by hypertension and anemia (10.0% each, n=150) which was comparable to the study by Padmawar et al [ 2 ]. This is in contrast to the work of Qureshi et al in which preeclampsia was observed in 14.6% (n=86) cases [ 3 ]. The variation may be due to differences in timing of presentation on which the diagnosis is largely dependent, besides severity of thrombocytopenia and the association with other abnormalities.…”
Section: Discussioncontrasting
confidence: 99%
“…Platelet indices are of significant discriminative value in differentiating the various causes of thrombocytopenia [ 11 ]. Qureshi et al showed placental abruption in 21.8% (n=86), postpartum hemorrhage in 14.6% (n=86) and maternal mortality in 2.1% (n=86) of these women [ 3 ]. Chauhan et al [ 12 ] reported that pregnancy-induced hypertension (PIH) was associated with 26.2% (n=65) of thrombocytopenic women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation